In Process of the Intelligent Organization Building - Krzysztof Kocurek (Contemporary Economics)
The starting point for the deliberations in this article is the issue of the key aspects and conditions of effective learning in the intelligent organization. The author briefly describes learning process that leads to the development and better use of knowledge in the enterprise. This article presents an analysis of the factors that determine new rules of knowledge management in the organization. The author focuses on the essence and attributes of knowledge-based organizations. In the final section of the article, the differences between the features of the traditional and knowledge age organizations are pointed out.